The network science approach in determining the intellectual structure, emerging trends and future research opportunities: An application to Tai chi for older adults - Pestana, M. H.; Sobral, M.; Wang, W.-C.; Parreira, A. (XVII International May Conference on Strategic Management IMCSM 2021, 2021)
This article focuses on the geriatric market segment which is becoming increasingly important as a result of demographic trends and aging populations. Using network science approach, this study maps the structure of knowledge, its changes over time and research opportunities in Tai-chi. Data collected from Web-of-Science and Scopus between 1996-2019 was used to build a network of 2,202 articles and 6,820 authors. The results show Tai-chi represents a small-world network as the majority of the articles were produced among universities and medical schools, displaying a connection between theoretical knowledge and pragmatic applications. The scientific achievements mainly emerge from the USA, China, and UK. The collaborative efforts focused on a giant component and converge on a small area of research. Future opportunities at the intersection of Tai-chi and geriatrics include mindfulness-meditation, osteoarthritis, sleep quality, cardio-respiratory function and pain management. This article provides contributes to the literature on Tai-chi and offers insights into the capabilities of CiteSpace, Vosviewer, Gephi, and Python.